2020
DOI: 10.3889/oamjms.2020.3531
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High- and Low-Frequency Repetitive Transcranial Magnetic Stimulation Therapy on Serum Brain-Derived Neurotropic Factor Level and Motor Ability in Ischemic Stroke Patients: A Single-Center Study

Abstract: BACKGROUND: Repetitive transcranial magnetic stimulation (rTMS) is widely used in various neurological cases. rTMS is an effective method of restoration in patients with disability due to central nervous system disorder. AIM: This study aimed to determine the effect of high and low frequency of rTMS on serum brain-derived neurotropic factor (BDNF) levels and motoric abilities in ischemic stroke patients. METHODS: The study design was an experiment with a purposive sampling consecutive on 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…For the effect of the rehabilitation on serum biomarkers in stroke patients, the meta-analysis revealed a moderate evidence, when compared to the control group. Furthermore, the concentration of brain-derived neurotrophic factor (BDNF) significantly increased in the treatment group, and this was significantly correlated to the functional improvement after stroke ( 10 , 14 , 15 , 28 , 34 , 36 , 41 , 47 , 48 ) ( Figure 2 ; Table 1 ). Compared to the control group, the low-quality evidence in the treatment group revealed that the concentration of serum noradrenaline (NE) increased ( 27 , 28 , 36 ), while the concentrations of serum endothelin (ET) ( 39 , 44 , 46 ) and glutamate ( 36 , 40 , 42 ) decreased, and these were significantly associated with the functional improvement after stroke ( Supplementary Figures S2–S4 ; Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the effect of the rehabilitation on serum biomarkers in stroke patients, the meta-analysis revealed a moderate evidence, when compared to the control group. Furthermore, the concentration of brain-derived neurotrophic factor (BDNF) significantly increased in the treatment group, and this was significantly correlated to the functional improvement after stroke ( 10 , 14 , 15 , 28 , 34 , 36 , 41 , 47 , 48 ) ( Figure 2 ; Table 1 ). Compared to the control group, the low-quality evidence in the treatment group revealed that the concentration of serum noradrenaline (NE) increased ( 27 , 28 , 36 ), while the concentrations of serum endothelin (ET) ( 39 , 44 , 46 ) and glutamate ( 36 , 40 , 42 ) decreased, and these were significantly associated with the functional improvement after stroke ( Supplementary Figures S2–S4 ; Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…The subgroup analysis based on the rehabilitation therapy revealed that there was a significant correlation with non-invasive brain stimulation (NIBS) therapy, but there was no correlation with no-NIBS ( 36 , 48 ) ( Supplementary Figures S7A,B ; Table 1 ). According to the treatment sessions for NIBS (five sessions vs. 10 sessions vs. 18–20 sessions vs. 30+ sessions), it was found that the serum BDNF concentration was significantly correlated with 18–20 sessions ( 10 , 14 , 28 , 47 ) and 30+ sessions ( 10 , 41 ), but this was not associated with five sessions ( 34 ) and 10 sessions ( 10 , 15 ) ( Supplementary Figures S7C ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After the precise data extraction for the time of sample collection regarding the stroke onset, we grouped the observation into five general groups. (1) Observations which compared baseline measures to the first day of the stroke, baseline vs day one or acute that covered four observations and 202 participants [ 32 , 39 , 59 , 60 ]; (2) Observations comparing the baseline measures to the peripheral level of BDNF within the first week of stroke onset (mostly 3–7 days) baseline vs week one or sub-acute, consisting of 14 observations and 1366 patients [ 32 , 39 , 42 , 44 , 54 , 56 , 59 , 61 67 ]; (3) Observations investigating the difference between baseline levels of BDNF and day 30 or above, baseline vs. over one month or chronic , that included 11 observations and 1093 participants [ 16 , 39 , 43 , 54 , 56 , 65 69 ]; (4) Comparison of the first day of the stroke to the first week after the onset, Day 1 vs Week 1 consisting three observations and 162 participants [ 32 , 39 , 59 ]; (5) Lastly the seven observations investigating the BDNF pattern, in 855 participants, within the first week of stroke and over the one months of affecting the patients [ 39 , 54 , 56 , 65 67 , 70 ].…”
Section: Resultsmentioning
confidence: 99%